From seafloor spreading to uplift: the structural and geochemical evolution of Macquarie Island on the Australian-Pacific plate boundary - Wertz, Karah Lynn (2003)
text Macquarie Island (54º30’S, 158º54’E) is unique, consisting of a section of uplifted oceanic crust and upper mantle that still lies within the ocean basin where it formed. Earlier geophysical studies indicate that between ~40 and 6 Ma, this plate boundary evolved from a spreading ridge to the modern transpressional boundary. The rocks of Macquarie Island record both regimes. This study combines structural, geochemical and geophysical data to describe the evolution of Macquarie Island and the adjacent Australian-Pacific plate boundary from spreading to transpression. The Finch-Langdon fault is the most significant spreading-related structure on the island, juxtaposing upper crust and intrusive/mantle rocks. On the basis of structural and petrologic data, I propose that this fault zone formed near the inside corner of a ridge-transform intersection (RTI) and that structures on the island are conformable with those in the surrounding seafloor. Geochemical data for Macquarie Island basalts and peridotites suggest a complex evolution during the last stages of seafloor spreading. The volcanic section consists of enriched basalts formed by low degrees of partial melting. Basalt geochemistry combined with stratigraphic relationships reveal early intervals of variable enrichment followed by periods of more constant, decreasing enrichment. Peridotite and basalt geochemistries differ distinctly. Peridotites show characteristics of a high degree of melting (heavy rare earth element, or REE, and Al depletion), whereas low degrees of partial melting are inferred for the basalts. The mantle rocks also have spoon-shaped REE patterns and anomalous Sr enrichment. The depletion and trace element patterns are more typical of mantle rocks in ophiolites than of abyssal mantle. Ridge propagation proximal to an RTI exposing lower crust/uppermost mantle would satisfy these structural and geochemical parameters. Subsequently, transpression along the Australian-Pacific plate boundary has resulted in transform motion along the plate boundary and vertical deformation along the ~1500 km long Macquarie Ridge Complex. Uplift faults on the island are dominantly high-angle, en echelon, normal faults. The geometries and kinematics of the faults do not match predicted fault patterns for transpression, but indicate domination by extensional relay zones between stepovers of faults along the plate boundary. Geological Sciences